La aventura de los molinos de viento: Innovación técnica. Recomposición textual. Valores en educación - González Landa, María del Carmen; Tejero Robledo, Eduardo (Didáctica. Lengua y Literatura, 2006)
This article offers a didactic treatment of Cervantes’ most remarkable text. It is about how to help students to understand it. It suggest proposals to develop ways of thinking and communicating. It passes along an interdisciplinary option in which language is the vehicle of an esthetic expression as well as scientific and technical one. Finally, it proposes certain messages in Don Quixote as transversal values in education.
Keywords: Knowledge; Understanding/Expression; Didactics; Language and Literature workshop; Values in Don Quijote; Education